Physical Geology - Earle, Steven; Open Textbook Library (Open Textbook Library, 2015)
Physical Geology is a comprehensive introductory text on the physical aspects of geology, including rocks and minerals, plate tectonics, earthquakes, volcanoes, glaciation, groundwater, streams, coasts, mass wasting, climate change, planetary geology and much more. It has a strong emphasis on examples from western Canada, especially British Columbia, and also includes a chapter devoted to the geological history of western Canada. The book is a collaboration of faculty from Earth Science departments at Universities and Colleges across British Columbia and elsewhere.
Chapter 1 Introduction to Geology -- Chapter 2 Minerals -- Chapter 3 Intrusive Igneous Rocks -- Chapter 4 Volcanism -- Chapter 5 Weathering and Soil -- Chapter 6 Sediments and Sedimentary Rocks -- Chapter 7 Metamorphism and Metamorphic Rocks -- Chapter 8 Measuring Geological Time -- Chapter 9 Earth's Interior -- Chapter 10 Plate Tectonics -- Chapter 11 Earthquakes -- Chapter 12 Geological structures -- Chapter 13 Streams and Floods -- Chapter 14 Groundwater -- Chapter 15 Mass Wasting -- Chapter 16 Glaciation -- Chapter 17 Shorelines -- Chapter 18 Geology of the Oceans -- Chapter 19 Climate Change -- Chapter 20 Geological Resources -- Chapter 21 Geological History of Western Canada -- Chapter 22 The Origin of Earth and the Solar System
In English.
Description based on print resource
Keywords: Earth Sciences -- Textbooks